What they don't know - Furlong, Susan (Seventh Street Books, 2022)
"Mona Ellison's life is as perfect as the porcelain dolls lined up on her shelves. She has a successful husband, a loving son, a beautiful home, and a supportive group of girlfriends ever ready for their weekly wine night. But when Mona's son gets entangled with the wrong crowd and runs away from home, her blissful suburban world begins to unravel. She tells her friends that boys will be boys, that he'll be back as soon as his money runs dry . . . but deep down she knows there's something else going on. Then the police show up at Mona's door. A young girl has turned up dead in their quiet town, and her missing son is the prime suspect. Determined to reunite with her son and prove his innocence, Mona follows an increasingly cryptic trail of clues on social media, uncovering a sinister side of suburbia and unveiling lies and betrayal from those she trusted most. And as Mona spirals further from her once cozy reality, a devastating revelation shatters everything she thought she knew. Now the only thing she's sure of is that she can't trust anyone... not even herself."--Back cover.